2016
DOI: 10.1002/2015jd024742
|View full text |Cite
|
Sign up to set email alerts
|

Dry deposition of particles to canopies—A look back and the road forward

Abstract: The so‐called accumulation‐size range of airborne particles is the center of a continuing disagreement about the formulation of dry deposition. Some contemporary meteorological and air quality models use theoretical developments based on early wind tunnel and other controlled experiments, while other models consider the bulk properties of the underlying surface and the ability of atmospheric turbulence to deliver particles to it. This dichotomy arose when the first micrometeorological measurements of particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 111 publications
(167 reference statements)
1
41
0
Order By: Relevance
“…Several studies have noted over recent years that the algorithms describing the size-dependent dry deposition of atmospheric particles over vegetative canopies do not agree very well with measurements, especially in the accumulation mode, and particularly for canopies with high surface roughness (Zhang and Vet, 2006;Petroff et al, 2008a;Pryor et al, 2008a). Recently, a review by Hicks et al (2016) surveyed the historical development of both the algorithms and measurements of this phenomenon, noting that measurements as far back as 1977 suggested a pronounced difference between measurements and modelderived expectations. Pryor et al (2008a) provided a thorough summary of potential explanations for the discrepancies, ranging from observational errors, to chemical RELATIONSHIP BETWEEN TURBULENT ENERGY DISSIPATION AND GAS TRANSFER 5 flux divergences, faulty model assumptions, or the neglect of important deposition processes (e.g.…”
Section: Models Of Atmospheric Particle Depositionmentioning
confidence: 99%
“…Several studies have noted over recent years that the algorithms describing the size-dependent dry deposition of atmospheric particles over vegetative canopies do not agree very well with measurements, especially in the accumulation mode, and particularly for canopies with high surface roughness (Zhang and Vet, 2006;Petroff et al, 2008a;Pryor et al, 2008a). Recently, a review by Hicks et al (2016) surveyed the historical development of both the algorithms and measurements of this phenomenon, noting that measurements as far back as 1977 suggested a pronounced difference between measurements and modelderived expectations. Pryor et al (2008a) provided a thorough summary of potential explanations for the discrepancies, ranging from observational errors, to chemical RELATIONSHIP BETWEEN TURBULENT ENERGY DISSIPATION AND GAS TRANSFER 5 flux divergences, faulty model assumptions, or the neglect of important deposition processes (e.g.…”
Section: Models Of Atmospheric Particle Depositionmentioning
confidence: 99%
“…However, dry deposition estimates for these species still have large uncertainties due to the many chemical, biological, and meteorological factors affecting dry deposition processes. Uncertainties for other chemical species are even larger (Fowler et al, 2009;Hicks et al, 2016;Mohan, 2016;Wesely & Hicks, 2000;Wright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Large uncertainties exist in modeled V d for fine particles (diameter around 0.1–1.0 μm) based on the comparisons of several dry deposition schemes (Hicks et al, ; Petroff et al, ; Pryor et al, ; Ruijgrok et al, ; Zhang & Vet, ), which can vary over 2 orders of magnitude. Previous studies that used wind tunnel measurements to optimize model simulations suggested that particles in the accumulation mode should have V d around 0.01 cm s −1 (e.g., Giorgi, ; Slinn, ), whereas studies based on field observations suggested much higher V d values (e.g., Allen et al, ; Gallagher et al, ; Grönholm et al, ; Sievering, ; Wesely et al, ).…”
Section: Introductionmentioning
confidence: 99%